Ancient Manuscript as Cultural Identity in The Community of Kabuyutan Ciburuy Bayongbong Garut Residence - Rodiyah, Saleha; Siti Khodijah, Ute Lies; Kurniasih, Nuning (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2017)
The background of documenting manuscript of Kabuyutan Ciburuy is related to the process of community understanding towards conducting preservation, real valueÂ of documenting and looking at the connection between documentation and efforts of preserving the cultural values embodied in the ancient manuscript. This study uses qualitative ethnographic approach. Data was collected through literature study, interview and observation. The result is that the ancient manuscripts can be maintained and prevented from damaging by storing them in proper temperature and humidity, and culturally maintained appropriately, besides understanding in the cultural context. Beside that, transforming to digital media is also done to avoid the old manuscripts from physical damage, although the contents are used for various purposes. Furthermore, the value of ancient manuscripts from this documentation is not only informative, historical and educational, but more culturally nuanced because the main purpose of this documentation activities aimed at developing the culture so that people of Kabuyutan Ciburuy understand the benefit value of ancient manuscript.